Cultural approximation, alienation and the role of English in Canadian society - Mohideen, Haja; Alam, Tasdiq Nomaira (Arab World English Journal (AWEJ), 2015)
The study examined the acculturation and adaptation of the immigrants in their new intercultural setting in Toronto, Canada, as well as the role of English language in their lives. The research made use of triangulation methods using three types instruments to collect data: structured questionnaire, open-ended questionnaire and interview. Sixty-four immigrants from different countries participated in the study. The findings indicate that the immigrants initially feel alienated and face numerous difficulties to adjust their lives in new and unfamiliar surroundings. But as soon as they acculturate, they feel contented although many impositions due to different social norms, lack of English proficiency, discrimination and stigma being immigrants often result in hindrance. The study also exposed the importance of English in the life of immigrants. Results show that well- educated and fluent English- speaking immigrants are more involved and accepted in Canadian society.